Pulmonary carcinoid presenting in pregnancy with an unusual radiological feature - Li, Anna (BMJ Case Rep, 2021)
Pulmonary carcinoid tumours are a rare form of malignancy that often present with clinical heterogeneity and are challenging to diagnose. Diagnosis during pregnancy is further complicated by delays in imaging and procedures to minimise harm to the fetus. This case describes a primigravid healthcare worker who was diagnosed with pulmonary carcinoid in her first trimester of pregnancy, with particular focus on the unique radiological findings of subpleural blebs as a feature.